2022
DOI: 10.1097/sap.0000000000003234
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Fat Grafting: An Institutional Retrospective Review

Abstract: Background Autologous fat grafting is a popular technique for volume replacement in the breast and face. The efficacy, safety, and complication rate of this technique at the division of plastic surgery at the University of Alabama at Birmingham will be described in this review. Methods An institutional review board–approved retrospective review of patients undergoing fat grafting procedures from January 2015 to July 2018 was performed. Records were revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Fat grafting in the breast has been proved to be a well-tolerated procedure [30,31]. Rates of major complications, such as hematoma, infection, and seroma, range from 2 to 3.6%, and are predominantly seen in cases where fat grafting was accompanied by reconstruction or revision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fat grafting in the breast has been proved to be a well-tolerated procedure [30,31]. Rates of major complications, such as hematoma, infection, and seroma, range from 2 to 3.6%, and are predominantly seen in cases where fat grafting was accompanied by reconstruction or revision.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, our review found a lower rate of common surgical complications following fat grafting than the rates mentioned above, potentially because most patients in this review underwent fat grafting as a standalone procedure. It is important to note that our review did not account for any additional procedures performed in conjunction with fat grafting that could contribute to surgical site complications [30]. One study recruited in this review, by Calabrese et al, likely contributes to heterogeneity due to its high rate of revision surgery [21].…”
Section: Discussionmentioning
confidence: 99%
“…"ASCs express β-1 integrin (CD29) which participates in angiogenesis and CD44 hyaluronate and osteopontin receptors, which are essential in the development of the extracellular matrix and pathological processes such as neoplasia" [3]. "In vitro and in vivo research show that ASCs are often found lining the outside of microvessels, and they have a stabilizing role by differentiating into pericytes and by expressing common pericyte surface proteins such as the smooth muscle late pericyte marker α-actin (α-SMA), neuronal/glial antigen 2 (NG2) or platelet-derived growth factor receptor β (PDGFRβ)" [8].…”
Section: Adipose-derived Stem Cells Angiogenesis In Fat Graftingmentioning
confidence: 99%
“…An intraoperative mechanical isolation procedure has been developed to produce tissue-derived stromal vascular fraction (tSVF) with more feasible clinical applications than enzymatic isolated Stromal Vascular Fraction [2]. There are 10.9% complications after fat grafting that have been reported and are considered serious, including hematoma, seroma, fat necrosis, dermatitis, cellulitis, and infection [3]. In this review we summarize the latest research and aim to provide an overview of ADSC angiogenesis in fat grafting, so that in the future research can be found that can avoid complications after fat grafting in breast reconstruction and provide satisfactory breast reconstruction results.…”
Section: Introductionmentioning
confidence: 99%
“…Autologous fat grafting is commonly used for a variety of reconstructive and aesthetic surgery procedures in the face, buttocks, and breasts. [1][2][3][4][5] The American Society of Plastic Surgeons reported that more than 155,000 cosmetic procedures involving fat grafting were performed in 2020. 6 In a clinical setting, one of the major challenges of autologous fat grafting is poor graft retention, ranging from 25% to 90% overall volume loss over time.…”
Section: Introductionmentioning
confidence: 99%